The analysis of teacher candidates’ teaching skill in department of biology education, University of Borneo Tarakan, through pre-service teaching activities - Fitri Wijarini; Silfia Ilma (JPBI (Jurnal Pendidikan Biologi Indonesia), 2017)
This study aimed to know pre-service student teaching skill on Biology education by PPL activities semester 2016/ 2017. This was descriptive research in which the subject were 27 students year 2013 in Biology education program. The research assessment instrument used was the rubric fulfilled by Pre-service teachers based on observational activity during three months. The data analysis technique were data presentation and conclusion of the study. The teaching skill components observed consist of 10 components. The results of 10 components including the skill in arranging learning scenario with the value of 86.79 (average), opening and closing learning skill of 86.41 (average), explaining skill of 85.67, question skill 86.6, providing reinforcement skill 87.11, using instructional media skill 87.03, held a variety skill of 84.9, discussion guiding skill of 85, assessment skill of 86.1, and classroom management skill 87.4. The overall average Biology Education student teaching skills are 83 which is categorized into good category.